Cameroon : Poverty Reduction Strategy Paper Implementation Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Cameroon's Poverty Reduction Strategy Paper Implementation Progress Report. Cameroon is expected to benefit from a significant debt relief upon reaching the completion point. This will make huge financial resources available to Cameroon for financing its growth and poverty alleviation policy designed in conformity with the new financial assistance programs of the Bretton Woods institutions. The downturn in inflation is a result of a substantial increase in the supply of food and market garden produce, the opening up of some agricultural zones, and a flow of imported staple consumer goods.